cuidado al recién nacido críticamente enfermo desde la perspectiva de la enfermera - Lara Núñez, Gloria Gladys (2019)
ABSTRACT Research with a qualitative approach, carried out in the Neonatology Service of the Victor Lazarte Echegaray Hospital in Trujillo-Essalud, whose purpose was to describe, analyze, understand and develop conceptual approaches on the care of the critically ill newborn, from the perspective of nurses, of the Neonatal Intensive Care Unit (ICU), which met the selection criteria of the participants, including the ethical criteria and scientific rigor and informed consent. The theoretical bases are based on the philosophical conceptions of the care of Watson and Waldow and of the perception of Merleau-Penty. The unstructured interview was used to collect the information; the sample was 16 nurses. In the analysis of information and the construction of the emerging theory, the Fundamental Theory method was used, applying open, axial and substantive coding; four coincident categories emerged; no divergent category was found. The resulting emergent theory considers the newborn as a center of care that requires skills and abilities of the Neonatal ICU nurse, to provide care as an act of love that implies a professional commitment of the nurse from the ethics of care.